Estratégias para implantação e avaliação de um método educacional desplugado com histórias em quadrinhos para o ensino e aprendizagem associados ao desenvolvimento do pensamento computacional com alunos do ensino fundamental - Santos, Cícero Gonçalves dos (2019)
Schools in the technology age need to reinvent themselves and stimulate the student to think critically, for this, it is necessary to use technology as a didactic resource that provides the formation of problems and solutions for them, using the fundamentals of the CT. In this way, the CT consists of knowing how to use computing in an interdisciplinary way as an instrument of increase to the cognitive power, contributing to the increase of productivity, inventiveness and creativity. However, the unplugged computation is presented as an alternative to assist in the development of the stimulus to the CT, without the direct use of computers. Thus, this dissertation proposes the use of comics with themes in CS, supported by the unplugged approach in the stimulation of the PC of elementary students, with the objective of creating, implementing and evaluating an Educational Guide Plan with Displaced Comic Stories that will help in the development of CT, logical reasoning and textual interpretation with elementary students in Portuguese and Mathematics. Believing in the hypothesis that the development of the CT applied to the disciplines and respective contents of Portuguese Language (textual interpretation) and Mathematics (logical reasoning), supported by pedagogical resources of teaching-learning Deployed contribute in a qualitative and quantitative way in the aid of the stimulus to the logical reasoning and textual interpretation of elementary school students. In view of this, in order to carry out this analysis, a descriptive study was adopted through bibliographical procedures, Survey, questionnaires, finally, experiments for validation of the proposed artifact, Guidelines Plan, with the intention of using comics of Almanacs for Popularization of Computer Science in a unplugged way, in order to help students of the 9th grade of Elementary Education to develop the CT. In this way, the validation of the artifact, which attends to the 4 pillars of the CT, has been obtained as results, assisting in the development of critical thinking, algorithm thinking, cooperative thinking, and problem solving. In this way, the artifact was validated by means of the resolution of a Questionnaire for Validation with 30 professionals from each area, CS, Letters - Portuguese Language and Mathematics, applied before & after the experiments. However, the experiments were carried out with 9th grade students from the public school system of the town of Olho d'Água do Casado-AL, during 9 meetings for each experiment: (Experiment 1) all students of one of 50 students participated directly in the proposed activities; and (Experiment 2) half of a class of 50 students participated directly in the activities proposed by the artifact developed. Therefore, an improvement in the school performance of the students who participated in the meetings regarding the experiment was identified. Thus, the proposed artifact assists in the teaching-learning process for the development of CT, textual interpretation and logical reasoning.